Reactivation of Ancient Landslide Deposits: Geological Characteristics and Deformation Mechanism - Rubin Wang; Kun Zhang; Yu Ning; Weiya Xu; Wenyuan Wang; Jianfu Qin (Advances in Civil Engineering)
The ancient Zhenggang landslide (47.5 million m3) represents a potential threat to the construction and safe operation of the proposed Gushui Hydropower Project and to the people living downstream. The landslide was caused by continuous rainfall from October 20 to November 5, 2008, indicating that groundwater aggravated sliding and deformation, and it can be divided into two distinct zones: zone I and zone II. Investigations of the Zhenggang landslide deposits have been conducted for 10 years, but the evolution of the landslide deformation is yet to be revealed. Geological surveys and stability analysis have revealed that the Zhenggang landslide is currently relatively stable and is not sliding. The deformational data for the deep soil layers show that subslide zone I is a translational slide, while subslide zone II is an uplift slide, and zone II is slightly more stable than zone I. Obvious interior deformational failure occurred and was observed in the exploratory adits. The numerical results show that rainfall infiltration is the main factor to induce the revival of ancient landslide, and it is necessary to strengthen the landslide risk assessment and reliability of Zhenggang landslide under the condition of rainfall infiltration. Finally, in order to reduce landslide risks, the local residents living near the landslide mass should be relocated, and measures should be taken to increase slope stability.